Proteinuria, 99mTc-DTPA Scintigraphy, Creatinine-, Cystatin- and Combined-Based Equations in the Assessment of Chronic Kidney Disease. (11th February 2014) - Trimarchi, Hernán; Muryan, Alexis; Toscano, Agostina; Martino, Diana; Forrester, Mariano; Pomeranz, Vanesa; Lombi, Fernando; Young, Pablo; Raña, María Soledad; Karl, Alejandra; Alonso, M.; Dicugno, Mariana; et al.
Abstract : Background . Precise estimation of the glomerular filtration rate (GFR) and the identification of markers of progression are important. We compared creatinine, cystatin, and combined CKD-EPI equations withTc-DTPA 99m scintigraphy to measure GFR and proteinuria as markers of progression. Methods . Cross-sectional, observational study including 300 subjects. CKD was classified byTc-DTPA 99m scintigraphy. Determinations . Creatinine, 24-hour creatinine clearance, cystatin, Hoek formula, and creatinine, cystatin, and combined CKD-EPI equations. Results . In the global assessment, creatinine CKD-EPI and combined CKD-EPI equations yielded the highest correlations withTc-DTPA 99m : ρ = 0.839, P < 0.0001 and ρ = 0.831, P < 0.0001 . Intergroup analysis versusTc-DTPA 99m : control G, creatinine clearance ρ = 0.414, P = 0.013; G3, combined CKD-EPI ρ = 0.5317, P < 0.0001 ; G4, Hoek ρ = 0.618, P < 0.0001, combined CKD-EPI ρ = 0.4638, P < 0.0001 ; and G5, creatinine clearance ρ = 0.5414, P < 0.0001, combined CKD-EPI ρ = 0.5288, P < 0.0001 . In the global assessment, proteinuria displayed the highest significant correlations with cystatin ( ρ = 0.5433, P < 0.0001 ) and cystatin-based equations (Hoek:ρ = - 0.5309, P < 0.0001 ). When GFR < 60 mL/min: in stage 3, proteinuria-cystatin ( ρ = 0.4341, P < 0.0001 ); proteinuria-Hoek ( ρ = −0.4105, P < 0.0001 ); in stage 4, proteinuria-cystatin ( ρ = 0.4877, P < 0.0001 ); proteinuria-Hoek ( ρ = −0.4877, P = 0.0026). Conclusions . At every stage of GFR < 60 mL/min, cystatin-based equations displayed better correlations withTc-DTPA 99m . Proteinuria and cystatin-based equations showed strong associations and high degrees of correlation.